Improved model for multiple uncorrelated Rayleigh fading channels - WANG Xin; FENG Guang-zeng (Tongxin xuebao)
An improved model for multiple uncorrelated Rayleigh channels was proposed.Compared with other models,this new model satisfied not only the stochastic characters of Rayleigh channel but also the uncorrelation between different fading channels.The simulation results show that the statistics for single channel of the new model is the same as other models and its uncorrelation is obviously better.